Analysis of household preferences on waste electrical and electronic equipment management - Rafia, Afroz; Akhtar, Rulia; Masud, Muhammad Mehedi; Duasa, Jarita (Inderscience Online, 2015)
The management of waste electrical and electronic equipment (WEEE) has become an environmental concern in Malaysia due to its rapid growth. To address this issue, we tried to investigate the relationship between household’s willingness to pay (WTP) and WEEE management system in Kuala Lumpur, Malaysia. In order to quantify household’s WTP for improved WEEE management system, we employed a contingent valuation method (CVM). The household’s WTP was then elicited through a series of face-to-face interviews of residents in 350 randomly selected households. The results showed that 73.52% of the households were willing to pay. The mean WTP was RM 23.47 ($8.09) per household monthly fee. In order to establish the relationship between endogenous variables and household’s WTP, a logistic regression model was constructed. It was found that education level, age and household income significantly affected households’ WTP for improving WEEE management system in Kuala Lumpur.